New aspects of organic chemistry II : organic synthesis for materials and life sciences : proceedings of the fifth International Kyoto Conference on New Aspects of Organic Chemistry - International Kyoto Conference on New Aspects of Organic Chemistry (5th : 1991 : Kyoto, Japan); Zen'ichi Yoshida; Yoshiki Ohshiro (aWeinheim : VCH, 1992)
42